WOMAN DISCRIMINATION IN OSCAR WILDE’S THE PICTURE OF DORIAN GRAY - Fanani, Abu; Eka Andini, Risky; Fidiyanti, Murni; Mohammad Romdlon, Atiq; Rosyidi, Zudan (LP3MKIL, 2024)
This study analyzes woman discrimination in Oscar Wilde’s The Picture of Dorian Gray and finds that the role of women has been marginalized in the eyes of men. Using a descriptive and dramatic method through which the researcher takes a look at the action as well as speech of the characters in the novel, the study finds that women are discriminated against because of objectification of women, oppression of women’s voices, emotional abuse as well as manipulation, and society's expectations and standards. Through this study, the researcher is in considerable hope that it will contribute to the development of literary studies, especially in the area of feminism.